MODEL PEMBELAJARAN RADEC UNTUK MENINGKATKAN HIGHER ORDER THINGKING SKILL DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Triska Rindiana; Muh. Husen Arifin; Yona Wahyuningsih (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2022)
In the development of science and technology in the 21st century, skills such as HOTS are very important. In Indonesia, its implementation in the HOTS field has not been fully achieved, due to the implementation of a learning model that is difficult for teachers to remember in its syntax. This study aims to determine the RADEC learning model to improve HOTS in social studies learning in elementary schools. The method used in this study is a systematic review, namely a review of previous studies. The result of this study is that HOTS in social studies learning becomes a very important thing that must be developed by teachers, because in the 21st Century HOTS is one of the most important skills students have to answer the challenges of the 21st century. One of the learning models that can be applied to improve HOTS is RADEC which starts from Read-Answer-Discuss-Explain-Create. These stages can clearly build HOTS because in the RADEC learning model students are required to analyze and create..